PENGARUH MOTIVASI KERJA DAN SELF EFFICACY TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL STUDI PADA SMA NEGERI KECAMATAN PATI, KABUPATEN PATI - Kusmiyatun, 12.52.02.0196; Suhari, Yohannes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This is a research which was done in the land, high school teachers in pati of starches and aims at: ( 1 ), the motivation to work and analyze the teacher organisasional ( 2 ), and analyzing impact on organisasional self-efficacy the teacher ( 3 ), and analyzing impact on the performance of the job and ( 4 ) and analyzed self-efficacy impact on the performance of ( 5 ) and analyzed organisasional test of the performance of the teachers, ( 6 ) the organisasional memediasi the role of teacher in the teacher s impact on the performance of ( 7 ), the role of teacher in organisasional memediasi self-efficacy influence on the teacher. This type of research is the research field (Field Reseach), using a quantitative approach. The population in this research is the teacher of government employees in high school country, Subdistrict Pati, Regency Pati, which amounted to 164 people. Samples were taken using the technique of the census. Technique of data analysis using regression analysis of liner model test, test, test R 2 F, hypothesis testing using t-test and test of mediation The results showed that in the scope of teacher high school country, Subdistrict Pati, Regency Pati, as follows; (1) significant positive effect of work Motivation of Organizational Commitment of teachers, (2) Self-Efficacy the significant positive impact on Organizational Commitment of teachers, (3) a significant positive effect of work Motivation on performance, (4) Teacher Self-Efficacy the significant positive effect on performance teacher, (5) Organizational Commitment of significant positive influence on performance of teachers, (6) Organizational Commitment does not mediate the influence of Work Motivation on teacher performance, (7) Organizational Commitment does not mediate the influence of Self-Efficacy on teacher performance . Keywords: Work Motivation, Self-Efficacy, Organizational Commitment and performance of the teacher.